Pengabdian Masyarakat Pelatihan Guru SMP Al-Imam Islamic School dalam Pembuatan Sistem Informasi Presensi Siswa Berbasis Android dengan Appsheet dan Spreadsheet - Faik Bajsair; Fauzi Baisyir; Ahmad Taufik (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This community service activity is a tangible form of the university's commitment to answering the challenges of the digital era. The issue and focus of this community service is that it is known that the manual attendance method that is still used by teachers is less effective in recording attendance, entry time, and lateness. Therefore, this study aims to implement a digital attendance information system to improve the accuracy and efficiency of attendance recording. Teacher training at Al-Imam Islamic School Junior High School aims to improve the student attendance system with an Android-based approach using AppSheets and Spreadsheets. The implementation of training on making an android-based student attendance information system with appsheets and spreadsheets at Al-Imam Islamic School Cileungsi Junior High School proved that teachers showed an increase in understanding related to the concept of making information systems, appsheets and spreadsheets, which included camera features, GPS, updated data in spreadsheets, to procedures for making applications using spreadsheets. Teachers learn that the attendance information system is not a difficult thing and in this day and age we are also required to enter the world of technology and digital to make teaching and learning activities easier and more fun, This increase in understanding is reflected in the results of pre-test evaluations and material presentations that show an increase in knowledge in understanding the concept of creating an android-based student attendance information system with appsheets and spreadsheets.